Medico-social rationale for the development of digital personnel potential in healthcare - Kriachkova, L.V.; Simon, K.I. (Medicni Perspektivi, 2025)
The digital transformation of the healthcare system is a key factor in improving the efficiency of medical services and sector management. One of the critical aspects of this transformation is the development of digital workforce potential, which includes the formation and enhancement of digital competencies among healthcare professionals. The aim of the study was to provide a medical and social justification and develop a conceptual model for the development of the digital potential of healthcare personnel to improve the sector's operational efficiency. A comprehensive approach was applied in the research, including a sociological survey of 162 healthcare professionals (practicing physicians, managers, and researchers), an analysis of strategic documents, the conceptual modeling method, and statistical analysis using standard tests conducted via Jupyter Notebook (https://jupyter.org). The findings indicate that the overall self-assessed level of digital competencies among healthcare professionals is moderate – 2.63 (95% CI 2.53-2.74) on a 5-point scale – suggesting potential for further growth. The highest competency level was recorded in general digital literacy, while the lowest was in digital tools and applications. Statistically significant differences were identified (p<0.001), as well as a positive correlation between the level of digital skills and the awareness of their importance for professional activities. The study identified the key stages in the cycle of forming, developing, and consolidating digital competencies among healthcare personnel while building digital human resource potential in healthcare. The most important stakeholder groups were also highlighted, with the top three, as identified by respondents, being: the Ministry of Health, higher medical education institutions, and healthcare institutions. Other key stakeholders include healthcare professionals and patients. Among the measures for developing digital competencies in healthcare personnel, respondents rated infrastructure development as the most significant at the systemic and organizational levels (over 40% of top ratings). A conceptual model for the digital potential of healthcare personnel in the healthcare system has been proposed. This model could serve as a foundation for developing further strategies in this area and contribute to achieving the primary goal of the sector – improving public health.